The menace of get rich quick syndrome among some Nigerian Youths: Changing the narrative through Social Studies Education - Bright Kelechi Uzoji; Muhammad Ridwan (Britain International for Academic Research (BIAR) Publisher, 2025)
The desire to get rich quick and live a lavished life style among Nigerian youths is becoming an issue of great concern. Today, the Nigerian youth who is supposed to be a beacon of hope is engaged in all manner of fraudulent activities with its negative consequences just to make ends meet. Thus, this paper identifies major types of ‘get rich quick’ schemes among Nigerian youths, highlights factors responsible for this ugly trend, it also discusses the rationale for mitigating the menace of ‘get- rick- quick’ syndrome through social studies education and the role of social studies education in curbing this nefarious activity. The paper concludes by proffering recommendations that would help reduce the incidences of ‘get- rich- quick’ syndrome; social studies as a corrective subject should continue to emphasize and advocate for the dignity of labour, there is a dire need for national reorientation of the Nigerian youth such that ethical values of honest living and hard-work are promoted.